Assessing Shifts in Research Priority Areas From the Neurological Community Before and After the COVID‐19 Pandemic. - Dempsey, Leah; Cruickshank, Travis; Turner, Mitchell; Laws, Manja; Bartlett, Danielle; Singer, Barby; van der Groen, Onno; Sim, Moira; Stanley, Mandy (Health Expectations, 2026)
Introduction: People living with a neurological condition face many difficulties in daily life, impacting their function and quality of life (QoL). There is currently no cure to many neurological conditions, therefore identifying interventions to improve QoL is of high importance. COVID‐19 changed society in many ways and understanding the research priorities from the neurological community post pandemic is urgently needed to ensure resources are used efficiently and aligned with the needs and priorities of the community. To better understand the priority areas, it is essential for individuals with lived experience to have input into priority areas for research. Therefore, the aim of this study was to identify the top research priorities for the neurological community in Australia. Methods: This priority setting study had two phases. The first phase comprised a face‐to‐face full day workshop held in late 2019 where participants were led through rounds of brainstorming, categorising and prioritising to reach consensus on a set of research priorities. The second phase was conducted in 2023 with an online survey distributed widely to gauge whether the initial set of research priorities had changed following the event of the global pandemic. Results: On completion of the 2019 workshop there were a total of 27 priority areas with the top priority being diagnosis and early intervention. The 2023 survey results saw mental health and wellbeing moving up one position to become the highest priority. Conclusion: Mental health and wellbeing moving from second in 2019 to first in 2023, shows a need for more resources and research into this area for the neurological community. Many participants suggested that mental health is at the centre of their condition and when their mental health is poor it impacts all areas of their life. The research priorities identified in this study provide direction for researchers about what is important to people living with a range of neurological conditions, allowing researchers to focus on the needs of this community. Patient or Public Contribution: The data collection phase was planned in collaboration with the Consumer and Community Health Research Network, a consumer advocacy organisation. We partnered with people living with neurological conditions for the data collection for both phases and they gave feedback on the findings.